A case of negative‐pressure pulmonary oedema after first‐time electroconvulsive therapy - Yasuhito Sekimoto; Yoshifumi Suzuki; Koichiro Kanamori; Isao Kobayashi; Hiroki Ienaga; Kazuhisa Takahashi (Respirology Case Reports, 2022)
Abstract Electroconvulsive therapy (ECT) has been used for many years as an important treatment modality in patients with schizophrenia. Recently, many new oral medications have become available to treat schizophrenia. However, ECT remains a valuable therapy for patients who are resistant to oral medications. A 16‐year‐old girl with schizophrenia was admitted to our hospital with hypoxaemia due to negative‐pressure pulmonary oedema (NPPE) after her first ECT. NPPE is an exceedingly rare complication after ECT. However, it can result in serious morbidity if not immediately recognized and treated. This case illustrates the importance of recognizing this rare complication.